EFL Students’ Speech Self – Efficacy at English Department of Universitas Negeri Padang - Zhiska Cladonia; Leni Marlina (Universitas Negeri Padang, 2021)
Some students feel scared when they have to perform speech in front of public. They feel a kind of tension, worry and discomfort during the speech performance. Therefore, this research was aimed to find the level of speech self – efficacy performed by students who had taken Public Speaking class at English Department of Universitas Negeri Padang. This research was a descriptive research. The population was second year students registered in the Public Speaking Class of English Language Educational Program. The sample was taken by using random sampling. It was a class from English Language Educational Program. The chosen sample consisted of 29 students. The data were collected through a questionnaire that consist of 8 items divide 48 questions of speech self – efficacy. The results of this study shows that the students’ level speech self-efficacy was medium. It means that the students need more self – efficacy to increase their self-efficacy and motivation in studying and to improve their ability in delivering speech.